1978
DOI: 10.1111/j.1600-0609.1978.tb02504.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Human Preleukaemia II In Vitro Colony Forming Capacity in Aregenerative Anaemia with Hypercellular Bone Marrow

Abstract: The colony and cluster forming capacity of bone marrow and mononuclear leucocytes and colony:cluster ratio (CCIR) was studied in 23 patients with resistant anaemia and hypercellular bone marrow. Bone marrow controls included 28 patients with iron deficiency, haemolytic, megaloblastic and secondary anaemia as well as 15 haematologically normal subjects and 13 healthy volunteers. Colony formation by blood leucocytes was studied in aregenerative anaemias and in 13 healthy volun‐Colonies and clusters were grown in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
4
0
1

Year Published

1979
1979
1996
1996

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 21 publications
2
4
0
1
Order By: Relevance
“…Granulocyte-macrophage colony formation in myelodysplastic syndromes has been in-vestigated in a number of studies (1)(2)(3)(4)(5)(6)(7)(8). The present results are in general similar to those obtained in previous studies, although the % of patients with normal CFU-GM colony formation was higher in this study than in most others.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Granulocyte-macrophage colony formation in myelodysplastic syndromes has been in-vestigated in a number of studies (1)(2)(3)(4)(5)(6)(7)(8). The present results are in general similar to those obtained in previous studies, although the % of patients with normal CFU-GM colony formation was higher in this study than in most others.…”
Section: Discussionsupporting
confidence: 90%
“…Myelodysplastic syndromes (preleukaemia) are a heterogenous and variably-defined group of disorders. The in vitro formation of colonies by granulocyte-macrophage progenitors from the marrow of patients with these diseases has been investigated in several studies, and abnormal growth patterns have been found in a varied proportion of patients (1)(2)(3)(4)(5)(6)(7)(8). The abnormalities are similar to those seen in acute myeloid leukaemia: reduced formation of colonies or excessive growth of colonies and/or smaller aggregates, clusters.…”
mentioning
confidence: 98%
“….7 pg/ml, RARS 11 k 5.8 pg/ml, CMML 12.5 f 3.7 pg/ml, RAEB 4.712.7 pg/ml, RAEB-t 4 . 0 1 2.3 pg/ml).In keeping with previous data reported in the literature(16)(17)(18)(19), growth of bone marrow HPC was significantly reduced (p <0.01) in MDS patients versus controls (CFU-GM: 26.1 1 8.1 colonies/2 x…”
supporting
confidence: 87%
“…When more adequate therapeutic measures become available, it should be of great value to identify patients who are liable to develop malignancy. The in vitro culture technique of cloning stem cells from the bone marrow is useful for identifying malignant patients, but does not differentiate preleukemic patients from those who die from cytopenic complications (2,16). A careful cytological evaluation in sequential bone marrow samples, using a simple scoring system a s outlined in the present study, can be a complementary method for identifying patients in the malignant group who are liable t o develop overt leukemia within a short time.…”
Section: Discussionmentioning
confidence: 95%